Application of computer-assisted navigation systems in oral and maxillofacial surgery. Issue 3 (August 2018) - Sukegawa, Shintaro; Kanno, Takahiro; Furuki, Yoshihiko
Summary: The oral and maxillofacial region has a complicated anatomy with critical contiguous organs, including the brain, eyes, vital teeth, and complex networks of nerves and blood vessels. Therefore, advances in basic scientific research within the field of intraoperative oral and maxillofacial surgery have enabled the introduction of the features of these techniques into routine clinical practice to ensure safe and reliable surgery. A navigation system provides a useful guide for safer and more accurate complex in oral and maxillofacial surgery. The effectiveness of a navigation system for oral and maxillofacial surgery has been indicated by clinical applications in maxillofacial trauma surgery including complex midfacial fractures and orbital trauma reconstruction, foreign body removal, complex dentoalveolar surgery, skull base surgery including surgery of the temporomandibular joint (TMJ), and orthognathic surgery. However, some fundamental issues remain involving the mobility of the mandible and difficulty in updating images intraoperatively. This report presents an overview and feasible applications of available navigation systems with a focus on the clinical feasibility of the application of navigation systems in the field of oral and maxillofacial surgery and solutions to current problems.